Introduksi Pembuatan Bioetanol Berbasis Pati dan Limbah Sagu di Kecamatan Sungai Tabuk, Banjar, Kalimantan Selatan - Mursyidin, Dindin H; Susilo, Tanto Budi; Badruzsaufari, Badruzsaufari; Nazari, Yudhi Ahmad; Tuhuloula, Abubakar (Universitas Lambung Mangkurat, 2024)
Starch and sago waste are some of the raw materials most prospective to be developed into bioethanol. This activity aims to provide technical assistance in making bioethanol from starch and sago waste for sago farming communities in Sungai Tabuk District, Banjar, South Kalimantan. This activity is carried out in two stages, namely socialization and technical assistance in making bioethanol from starch and sago waste, as well as monitoring and evaluation. Technical socialization and assistance, including internal monitoring and evaluation, have been carried out by the implementation team for target communities. A total of 24 farmers who are members of sago cooperatives in the local area participated in socialization activities and technical assistance in making bioethanol from starch and sago waste. They were very enthusiastic to participate in the activity, as seen from the atmosphere of the discussion and the results of the questionnaire they filled out. In the next activity, several people were accompanied and intensively trained to make bioethanol using tools designed and made by the implementation team. As a result, these activities generally meet the targets and outputs of this activity, namely: (1) Increasing insight of sago farmers in Sungai Tabuk sub-district, South Kalimantan to utilize the starch and sago waste they produce into bioethanol products; (2) The establishment of a pilot project to make bioethanol from starch and sago waste on a small industrial scale managed by sago farming communities; (3) Good cooperation between the implementation team and the local sago farmers, and (4) Bioethanol products produced from starch and sago waste with unknown concentration levels.